Tissue-type plasminogen activator-binding RNA aptamers inhibiting low-density lipoprotein receptor family-mediated internalisation - Bjerregaard, Nils; Bøtkjær, Kenneth A.; Helsen, Nicky; Andreasen, Peter A.; Dupont, Daniel M. (Thrombosis and Haemostasis, 2015)
Recombinant tissue-type plasminogen activator (tPA, trade name Alteplase), currently the only drug approved by the US Food and Drug Administration and the European Medicines Agency for the treatment of cerebral ischaemic stroke, has been implicated in a number of adverse effects reportedly mediated by interactions with the low-density lipo-protein (LDL) family receptors, including neuronal cell death and an increased risk of cerebral haemorrhage. The tissue-type plasminogen activator is the principal initiator of thrombolysis in human physiology, an effect that is mediated directly via localised activation of the plasmin zymogen plasminogen at the surface of fibrin clots in the vascular lumen. Here, we sought to identify a ligand to tPA capable of inhibiting the relevant LDL family receptors without interfering with the fibrinolytic activity of tPA. Systematic evolution of ligands by exponential enrichment (SELEX) was employed to isolate tPA-binding RNA aptamers, which were characterised in biochemical assays of tPA association to low density lipoprotein receptor-related protein-1 (LRP-1, an LDL receptor family member); tPA-mediated in vitro and ex vivo clot lysis; and tPA-mediated plasminogen activation in the absence and presence of a stimulating soluble fibrin fragment. Two aptamers, K18 and K32, had minimal effects on clot lysis, but were able to efficiently inhibit tPA-LRP-1 association and LDL receptor family-mediated endocytosis in human vascular endothelial cells and astrocytes. These observations suggest that coadministration alongside tPA may be a viable strategy to improve the safety of thrombolytic treatment of cerebral ischaemic stroke by restricting tPA activity to the vascular lumen.
Keywords: Fibrin clot lysis time; low density lipoprotein receptor-related protein-1; nucleic acid aptamer; stroke; tissue-type plasminogen activator